Phytochemical investigations and antiproliferative secondary metabolites from Thymus alternans growing in Slovakia. (1st January 2017) - Dall'Acqua, Stefano; Peron, Gregorio; Ferrari, Sara; Gandin, Valentina; Bramucci, Massimo; Quassinti, Luana; Mártonfi, Pavol; Maggi, Filippo
Abstract: Context: Thymus alternans Klokov (Lamiaceae) is a neglected species of the genus Thymus (Sect. Serpyllum ) endemic to Carpathian area, where it is used as a flavouring agent and for medicinal purposes. Objective: The aim of the work was to identify antiproliferative constituents from the flowering aerial parts of this plant. Materials and methods: Thymus alternans extracts were analyzed by HPLC-MS n and subjected to extensive chromatographic separations. The isolated compounds (phenolics and triterpenes) were structurally elucidated by MS and 1D and 2D NMR experiments. Essential oil (EO) composition was determined by GC-FID and GC-MS. Six purified triterpenes and EO were assayed for in vitro antiproliferative activity against a panel of human cancer cells, namely, breast (MDA-MB 231), colon (HCT-15 and HCT116), lung (U1810), pancreatic (BxPC3), melanoma (A375) and cervical carcinoma (A431) cells. Results: The structures of the isolated compounds were achieved on the basis of H-NMR and MS experiments. Luteolin-4′- O -β-d -glucopyranoside (P1), chrysoeriol-7- O -β-d -glucopyranoside (P2), chrysoeriol-5- O -β-d -glucopyranoside (P3), apigenin-7- O -β-d -glucopyranoside (P4), rosmarinic acid (P5), rosmarinic acid-3′- O -β-d -glucopyranoside (P6), caffeic acid-3- O -β-d -glucopyranoside (P7), 3 α -hydroxy-urs-12, 15-diene (T1), α-amyrin (T2), β-amyrin (T3), isoursenol (T4), epitaraxerol (T5), and oleanolic acid (T6). GC-MS analysis revealed that the EO of T. alternans was devoid of phenols and belonged to the nerolidol-chemotype, that is typical of the Sect. Serpyllum . The six purified triterpenes (T1-T6) were active with IC50 ranging from 0.5 to 5 μM being comparable or better than those of reference compounds betulinic acid and cisplatin. The EO exhibited significant effects on A375, MDA-MB 231 and HCT116 cell lines with IC50 in the range of 5–8 μg/mL. Conclusion: The reported results suggest that T. alternans can be considered as a good source of phytoconstituents with possible importance in the pharmaceutical field.